The Shapes of Neutrality. EU Enlargement, Engagement and Kosovo’s European Path - Dren Doli; Zamira Xhaferri (European Journal of Risk Regulation)
The article examines the European Union’s neutrality toward Kosovo’s statehood and its influence on the EU’s enlargement process and engagement strategy in view of internal divisions among the EU Member States over Kosovo’s recognition. It assesses how the EU’s mantra of neutrality shapes the dimensions of EU actorness, balancing differences among EU Member States while ensuring Kosovo’s inclusion in the EU enlargement process. Next, the article explores how the EU engages with Kosovo despite the lack of unanimous recognition of Kosovo’s statehood from five EU Member States, arguing that neutrality unfolds both as a legitimising principle and an authorisation mechanism. Our hypothesis is that neutrality has enabled Kosovo’s incremental involvement in the enlargement process without undermining the EU’s internal cohesion. Drawing on three illustrative examples, notably, the EU Rule of Law Mission in Kosovo, the Stabilisation and Association Agreement and the CJEU’s interpretation of EU-Kosovo SAA Agreement, the article demonstrates the variations of the concept of neutrality and its impact in maintaining Kosovo’s attachment to enlargement policy. The findings suggest that neutrality has been instrumental in authorising the EU missions in Kosovo and in sustaining Kosovo’s European trajectory.